Evaluation of extremely asymmetric types of distributions of geofeatures values - Kurmankozhayev, Azimkhan; Syzdykova, Guldana (Geodesy and Cartography, 2015)
"Corrigendum." Geodesy and Cartography, 41(4), p 185